Touch behavior based age estimation toward enhancing child safety - Hossain, M.S.; Haberfeld, C. (IJCB - IEEE/IAPR Int. Jt. Conf. Biom., 2020)
Adult content on the Internet may be accessed by children with only a few keystrokes. While separate child-safe accounts may be established, a better approach could be incorporating automatic age estimation capability into the browser. We envision a safer browsing experience by implementing child-safe browsers combined with Internet content rating similar to the film industry. Before such a browser is created it was necessary to test the age estimation module to see whether acceptable error rates are possible. We created an Android application for collecting biometric touch data, specifically tapping data. We arranged with an elementary school, a middle school, a high school, and a university and collected samples from 262 user sessions (ages 5 to 61). From the tapping data, feature vectors were constructed, which were used to train and test 14 regressors and classifiers. Results for regression show the best mean absolute errors of 3.451 and 3.027 years, respectively, for phones and tablets. Results for classification show the best accuracies of 73.63% and 82.28%, respectively, for phones and tablets. These results demonstrate that age estimation, and hence, a child-safe browser, is feasible, and is a worthwhile objective. © 2020 IEEE.
4 citations (Crossref) [2023-10-31] Journal Abbreviation: IJCB - IEEE/IAPR Int. Jt. Conf. Biom.
Keywords: Age estimation; Android applications; Behavior-based; Biometrics; Elementary schools; Entertainment industry; Feature vectors; Internet content; Mean absolute error; Telephone sets; User sessions; dept.csc